A new vector for recombination-based cloning of large DNA fragments from yeast artificial chromosomes. - Bradshaw, M S (1995)
The functional analysis of genes frequently requires manipulation of large genomic regions embedded in yeast artificial chromosomes (YACs). We have designed a yeast-bacteria shuttle vector, pClasper, that can be used to clone specific regions of interest from YACs by homologous recombination. The important feature of pClasper is the presence of the mini-F factor replicon. This leads to a significant increase in the size of the plasmid inserts that can be maintained in bacteria after cloning by homologous recombination in yeast. The utility of this vector lies in its ability to maintain large fragments in bacteria and yeast, allowing for mutagenesis in yeast and simplified preparation of plasmid DNA in bacteria. Using PCR-generated recombinogenic fragments in pClasper we cloned a 27 kb region from a YAC containing the Hoxc cluster and a 130 kb region containing the entire Hoxb cluster. No rearrangements were seen when the recombinants in the shuttle vector were transferred to bacteria. We outline the potential uses of pClasper for functional studies of large genomic regions by transgenic and other analyses.